Prevalence of vitamin B12 deficiency in Indian type 2 diabetes subjects on metformin therapy - R. Anil Kumar; Surekha B. Shetty; Lalitha R (International Journal of Medical Research and Review, 2017)
Background: To find out the prevalence of vitamin B12 deficiency in Indian type 2 diabetes subjects on metformin therapy.Material Methods: 161 type 2 diabetes subjects were studied over a period of 6 months at Karnataka institute of endocrinology Bangalore. All subjects gave written informed consent. BMI, Waist circumference, FPG, PPPG and HBA1c were estimated. Vitamin B12 levels were estimated by electrochemiluiminescence. We have excluded patients taking alcohol, vitamin B12 supplements, pregnant woman, and type 1 diabetics. Subjects whose vitamin B12 less than 200 picogram/ml were considered to be deficient in vitamin B12. Subjects who were on metformin treatment for more than 6 months were included in the study.Results: 118 diabetes subjects were males. They were in the age group of 30 to 80 years. Duration of diabetes was 1 to <5 years in 20.5%, 5 to <10 years in 28.5% and 10 years and morein 51% of diabetes subjects studied respectively. 55.9% of subjects had positive family history of type 2 diabetes. 112 subjects were on 1000 mg metformin for one year or more and 49 were on 2000 mg metformin for one year or more. Prevalence of vitamin B12 deficiency was 27.33%.Conclusions: The prevalence of vitamin B12 deficiency is 27.33% in type 2 diabetes subjects on metformin therapy. The percentage of deficiency increased with increase in dosage of metformin but there was no correlation to duration of metformin therapy.